Artifex and ulteriority of representation in Bonaventure (Itinera, 2021)
The article intends to investigate the capacity of representation to refer to further meanings in the thought of Bonaventure of Bagnoregio (1217/21-1274), starting from the Dino Formaggio’s conception of the ways of meaning in art: art is communication because it signifies in a plurivocal, plurivalent and uni-situational way. According to Bonaventure, natural and artificial things, as creation of the poietic activity of divine and human artifex, refer to further meanings also by the attitude of the observer that can consider the image as that which refers to a univocal sensible meaning, or as that which refers to an ulteriority, a multiplicity of spiritual senses. The Bonaventure’s idea of the ulteriority of representation arises also in the Franciscan art of the 13th and the 14th century and, with the emergence of the consciousness of the artist during this period, can confirm also from an historical point of view the conception of communication in art proposed by the Italian philosopher Dino Formaggio.
Keywords: Poiesis, representation, image, Bonaventure, Dino Formaggio